2022
DOI: 10.7759/cureus.30738
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Regarding Ionizing Radiation Exposure Safety Among Orthopedic Surgeons at Hospitals in Al-Madinah

Abstract: Background and objectiveThe use of radiation imaging techniques in operation theaters is essential for numerous surgical procedures and patients' overall well-being. Radiation imaging techniques enable the surgeon to have a real-time visualization of the anatomy and to perform operations with a greater chance of success, decrease rates of patient morbidity, and enable surgeons to obtain imaging records before the patient leaves the theater room. However, with the increased use of imaging techniques in orthoped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…protective equipment and comply with radiation safety during the procedure (Thambura & Vinette, 2019). in this study, all nurses took precautions to protect themselves from radiation during the ERcp procedure and mostly used lead aprons, thyroid protectors, and lead glasses, and this was similar to the literature (alshabi et al, 2022;ardıç & S ¸ahin, 2022;avcı, 2016;Gül et al, 2019;Vural et al, 2012).…”
Section: (Continued)supporting
confidence: 54%
“…protective equipment and comply with radiation safety during the procedure (Thambura & Vinette, 2019). in this study, all nurses took precautions to protect themselves from radiation during the ERcp procedure and mostly used lead aprons, thyroid protectors, and lead glasses, and this was similar to the literature (alshabi et al, 2022;ardıç & S ¸ahin, 2022;avcı, 2016;Gül et al, 2019;Vural et al, 2012).…”
Section: (Continued)supporting
confidence: 54%
“…And in case you were wondering, a study by Alshabi et al focused on orthopedic surgeons and confirmed that the lack of knowledge and awareness of radiation safety is not limited to our specialty. 5 Despite these findings and quotes, there is hope. Weld et al studied the effect of safety, minimization and awareness radiation training (SMART) in urology residents performing ureteroscopy, finding that SMART decreased fluoroscopy times by 56%.…”
mentioning
confidence: 99%